Peran Harmony Dan Keinginan Untuk Berkembang Terhadap Keterlibatan Karyawan Dalam Organisasi - Mega Asri Zona (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2020)
This research aims to examine the effect of harmony and growth need strength towards employee involvement. Employee involvement plays an important role in maintaining employee long-term relationship with the organization. In this research harmony a dimension of trust which has direct and indirect influence on the organization. The direct influence of trust can be seen in attitudes, cooperation, behavior and performance at work. Meanwhile, although the relationship of growth need strength with employee involvement is well recognized, the reciprocal relationship between these constructs has never been tested in depth. This research uses a survey method to collect data through questionnaires. The sample in this study consisted of 62 respondents who came from different occupational backgrounds. Harmony and growth need strength directly influences employee involvement. It is interesting to observe when individuals with high growth needs strength and high harmony develop relationships based on social exchange theory. The results of this research found a direct influence between harmony and the growth need strength with employee involvement.